Study on serum iron profile in COVID-19 associated mucormycosis patients - Khan, Imran; M., Raghavendra B.; S., Vishal (International Journal of Research in Medical Sciences, 2022)
Background: Mucormycosis is an angio-invasive disease caused by fungi prevalence of which in India is approximately 0.14 cases per 1000 population. The incidence of mucor in COVID 19 patients has increased to greater extent. Probable cause of which is increased serum ferritin among these patients and Iron is required by virtually all microbial pathogens for growth and virulence. Hence, we had conducted a study to estimate serum iron profile and association of iron profile with mucor mycosis in covid-19 associated mucormycosis. Methods: Cross sectional study conducted from May 2021 to July 2021 by the department of general medicine, Banglore medical college and research centre, Karnataka. The data collected was analyzed statistically using descriptive statistics. Results: We observed increased prevalence of mucor cases among the patients aged between 41 to 60 years and those who were not vaccinated. Hyperglycaemia had strong correlation with development of mucor. There was lower UIBC, lower TIBC, high ferritin and serum Iron levels among those who had developed mucormycosis. Conclusions: By our observations, we concluded that the increased serum iron, ferritin, transferrin and reduced TIBC and UIBC are the associated risk factor in the development of COVID 19 associated invasive mucor mycosis. Patients with HbA1c >7 are at higher risk of developing COVID 19 associated mucor mycosis.